2008
DOI: 10.2746/095777308x272085
|View full text |Cite
|
Sign up to set email alerts
|

A technique for computed tomography (CT) of the foot in the standing horse

Abstract: Summary Computed tomography (CT) in equine orthopaedics is currently limited because of the price, availability, impossibility to transport the scanner into surgical theatre, and the contraindications of general anaesthesia in some patients. A pQCT (peripheral quantitative computerised tomography) scanner was designed by the authors to image the limbs of the horse, both in standing or recumbent position. Standing computed tomography of the foot with a pQCT scanner is feasible and well tolerated by the horse. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 17 publications
0
54
0
1
Order By: Relevance
“…The locations of periosteal callus that bridged the fractures in Quarter Horses in the study reported here are consistent with locations in Thoroughbreds reported elsewhere. 52,53 Rehabilitation of affected horses is likely to result in a return to full performance. Index of suspicion should be high for characteristic locations of stress remodeling lesions within bones.…”
Section: Discussionmentioning
confidence: 99%
“…The locations of periosteal callus that bridged the fractures in Quarter Horses in the study reported here are consistent with locations in Thoroughbreds reported elsewhere. 52,53 Rehabilitation of affected horses is likely to result in a return to full performance. Index of suspicion should be high for characteristic locations of stress remodeling lesions within bones.…”
Section: Discussionmentioning
confidence: 99%
“…However, CT scanning of the foot in the standing horse using a gantry in a horizontal orientation has been performed [33]. Results of the present study suggest that this approach to equine CT imaging needs to be expanded to include the fetlock.…”
Section: Discussionmentioning
confidence: 97%
“…Preservations of flexible models of hollow organs and many dried anatomical specimens were prepared (Arnautovic et al, 2005;McKiernan & Kneller, 1983;Updike & Holladay, 1986). Many studies to learning sectional anatomy by computed tomography (CT), magnetic resonance imaging (MRI), contrast radiography, ultrasonography and cadaver sectional anatomy (Alsafy et al, 2013(Alsafy et al, , 2014Alsafy, 2008;Desbrosse et al, 2008;Garland et al, 2002;Morgan et al, 2006;Puchalski, 2012 Table I. Percentages of student's perception of the educational design and content (Q1-Q10) as well as overall perception of Equine Anatopedia (Q11-Q20).…”
Section: Discussionmentioning
confidence: 99%